(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Soft Sensors (SS) provides an alternative way to the conventional aid for the process of acquiring vital control variables, process monitoring and other functions that are associated with process control. Realizing these soft sensors on different hardware gains more importance for optimized process output. Different hardware like field programmable gate arrays (FPGAs), processors, distributed and heterogeneous architectures, on chip devices are available at present. This paper presents a description about soft sensors in industrial process control and different hardware realizations of soft sensors that are used in industrial applications. Later in this paper, an approach based on neural network is proposed for realizing a soft sensor to estimate ethanol concentration in a bioreactor. Additionally this soft sensor is realized on System on Chip (SoC) hardware. This device features hardware/software co-design approach that provides flexibility in design. The hardware output values of ethanol are compared with true values that are calculated from laboratory analysis and simulation output.